2006
DOI: 10.1158/0008-5472.can-05-4352
|View full text |Cite
|
Sign up to set email alerts
|

Combination of a Fusogenic Glycoprotein, Prodrug Activation, and Oncolytic Herpes Simplex Virus for Enhanced Local Tumor Control

Abstract: We have previously developed an oncolytic herpes simplex virus-1 based on a clinical virus isolate, which was deleted for ICP34.5 to provide tumor selected replication and ICP47 to increase antigen presentation as well as tumor selective virus replication. A phase I/II clinical trial using a version of this virus expressing granulocyte macrophage colony-stimulating factor has shown promising results. The work reported here aimed to develop a version of this virus in which local tumor control was further increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 26 publications
(27 reference statements)
2
63
1
Order By: Relevance
“…[1][2][3][4][7][8][9][10][11][12][13][14][15] In this study, we demonstrate that HERV-W FMGs' cytotoxicity resulting from the formation of gigantic cells is sufficient to induce tumor regression, with a very strong bystander effect, after non-viral, intratumoral gene delivery as previously described for GALV.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…[1][2][3][4][7][8][9][10][11][12][13][14][15] In this study, we demonstrate that HERV-W FMGs' cytotoxicity resulting from the formation of gigantic cells is sufficient to induce tumor regression, with a very strong bystander effect, after non-viral, intratumoral gene delivery as previously described for GALV.…”
Section: Discussionmentioning
confidence: 74%
“…[4][5][6][7] In addition to this syncytia-mediated toxicity, FMG has also been shown to enhance the antitumor therapeutic activity of replicating adenovirus, oncolytic HSV and vesicular stomatitis virus. [8][9][10][11][12] FMG-induced cytotoxicity is not immediate. Multinucleated syncytia develop within 24 h after transfection and gradually die in 5 days.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] Various FMGs have been evaluated as a means to increase the potency of oncolytic viruses. 4,6,[12][13][14][15][16] Expression of the HIV gp120 FMG by a replicative adenovirus enhanced viral release and facilitated dispersion of virus particles through a culture of tumor cells in vitro. 4 In addition, a more recent report demonstrated that coinjection of plasmid DNA encoding the hyperfusogenic form of the GALV envelope glycoprotein significantly enhanced the in vivo efficacy of the adenovirus therapy.…”
mentioning
confidence: 99%
“…3), an oncolytic HSV-1 termed OncoVEX GALV/CD double-armed with yCD/uracil phosphoribosyltransferase fusion and GALV.fus has been created. 39 In Fischer f344 rats bearing subcutaneous 9L glioma, OncoVEX GALV/ CD proved most efficacious compared with the control viruses (OncoVEX, OncoVEX GALV or OncoVEX CD ) when combined with systemic 5-FC administration. Han et al recently created an oncolytic HSV-1, with double deletions in the γ34.5 and a47 genes, armed with tumor necrosis factor alpha (TNFa).…”
Section: Armed Oncolytic Hsv-1 With Other Antitumor Functionsmentioning
confidence: 95%